2020
DOI: 10.1002/cncr.33003
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival among 5‐year survivors of adolescent and young adult cancer

Abstract: BACKGROUND: Although there are a growing number of survivors of adolescent and young adult (AYA) cancer, to the authors' knowledge the long-term overall survival (OS) patterns for AYA cancer survivors are underreported. The objective of the current study was to assess the long-term survival of AYA cancer survivors and identify factors associated with diminished long-term survival. METHODS: The authors used The University of Texas MD Anderson Cancer Center's tumor registry to identify 5-year survivors of cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…As in previous studies, survival outcomes in the past (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999) were around 6% higher in female AYAs, but have become approximately equal between both sexes in 2010-2016 [12,14,55]. Lower survival outcomes among male AYAs in the past have been attributed to the increased burden of cancers related to the HIV/AIDS epidemic, which mainly affected males and historically had among the lowest survival outcomes (Kaposi sarcoma) [9].…”
Section: Kaposi Sarcoma and Non-hodgkin Lymphomasupporting
confidence: 57%
See 2 more Smart Citations
“…As in previous studies, survival outcomes in the past (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999) were around 6% higher in female AYAs, but have become approximately equal between both sexes in 2010-2016 [12,14,55]. Lower survival outcomes among male AYAs in the past have been attributed to the increased burden of cancers related to the HIV/AIDS epidemic, which mainly affected males and historically had among the lowest survival outcomes (Kaposi sarcoma) [9].…”
Section: Kaposi Sarcoma and Non-hodgkin Lymphomasupporting
confidence: 57%
“…Favourably high survival outcomes and promising gains among AYA cancer patients have been reported by multiple studies worldwide and now often exceed well above 80% (here 86.4% in 2010–2016) at five-years of follow-up [ 12 , 24 , 25 , 55 ]. As noted in a recent study, AYAs now demonstrate survival gains that are at least equal to those found in paediatric and older adult patient populations and it was concluded that the AYA survival gap has been closed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AYA cancer survivors have an inferior 5-year OS compared with the general population, while the long-term survival of AYA cancer survivors has improved[ 17 ]. However, the improvements of the survival rate and mortality of AYA cancer patients are not as good as those of younger or older patients, mainly because past oncologists and researchers did not pay attention to AYA cancer patients and there are few clinical studies on them[ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Due to delays in diagnosis and other biological factors, the 5-year survival for this cohort has stayed stagnant over the years despite improvements in the survivorship profile for pediatric and older adult cancer populations. 4-6…”
Section: Introductionmentioning
confidence: 99%